Exploring the influence of service-learning on achieving SDGs among HEI students: A case study - Caldea, Jimi D. (Animo Repository, 2023)
Service-learning (SL) is a practical approach to achieving the United Nations Sustainable Development Goals (SDGs). Literature on the connection between SL and the SDGs indicates that SL can contribute to the SDGs in many ways. However, SL’s influence on students’ commitment to responding further to the challenges of SDGs after taking a course with the SL component has yet to be explored. It uses a case study approach, following 40 undergraduate students at De La Salle University undergraduate students. It aims to study their critical learnings and plans of action relative to SDGs. Data were collected from classroom reflection sessions and journal papers. Data were analyzed using thematic analysis. On students’ critical learning, the study revealed that they have an improved understanding of the SDGs, a better comprehension of complex social issues, a need to be more socially available, and an increased determination to take action. On students’ plans of action after taking SL, both as a student and a professional, they have acknowledged the need to have continuous learning and reflection activities with their peers, take advantage of any chances to participate in ongoing efforts, incorporate SDGs in their business philosophy and professional practices, and continue to advocate and take the lead. This study established students’ articulation of various SL learnings and commitment to carry out different initiatives to further respond to SDGs’ challenges even after their SL program.